EVACUATION AND DISTRIBUTION OF THE POPULATION TO THE UZBEK SSR - Madina Muradovna Abdurakhmanova (Journals Park Publishing, 2023)
This article highlights the regulations adopted during the Second World War to regulate evacuation processes. Based on the analysis of archival documents, scientific and fiction literature, as well as the memoirs of people who survived the evacuation, the geography of distribution and placement of the evacuated population in the Uzbek SSR is revealed.
Keywords: Evacuation, Evacuation Council, organized and unorganized evacuation, rail transport, evacuation points, evacuation departments, distribution, placement.